Do guest worker programs give firms too much power? - Peter Norlander (IZA World of Labor, 2021)
Guest worker programs allow migrants to work abroad legally, and offer benefits to workers, firms, and nations. Guest workers are typically authorized to work only in specific labor markets, and are sponsored by, and must work for, a specific firm, making it difficult for guest workers to switch employers. Critics argue that the programs harm host country citizens and permanent residents ("existing workers"), and allow employers to exploit and abuse vulnerable foreign-born workers. Labor market institutions, competitive pressures, and firm strategy contribute to the effects of migration that occur through guest worker programs.
Keywords: J42; J61; J62; F22; 330; guest workers; migration; firms; monopsony; mobility